The Effect Of Purple Sweet Potato Flour Substitution On The Quality Of Lidah Kucing Cookies - D, Sri Wahyuni; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The background of this research is to vary the cat's tongue cookies with purple sweet potato flour which aims to utilize local food ingredients, add to the innovation of cat tongue cookies products.The main ingredient in making cat's tongue cookies is wheat flour which is still imported. This study aims to analyze the quality (volume, shape, color, aroma, texture and taste) of cat tongue cookies substituted with purple sweet potato flour as much as 20%, 40% and 60%. This type of research is a pure experiment with Completely Randomized Design (CRD) method. The data used are primary data obtained directly from 3 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of cat tongue cookies with purple sweet potato flour. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount F table, then it is continued with Duncan's test. The results showed that the substitution of purple sweet potato flour had an effect on the quality of volume and aroma, while for the quality of shape, color, texture and taste there was no significant effect. purple sweet potato as much as 40%.